Where’s My Tree? Virtue Ethics as a Pathway to Reduce Loss of Place and Animal Suffering - Brando, Sabrina (Journal of applied animal ethics research, 2025)
This paper discusses the role of zoos and aquariums (ZOAQs) in addressing ‘loss of place’, which we see as a convergence of habitat destruction, biodiversity loss (species extinction), and animal suffering. Employing the metaphor of philosophical plumbing, this paper reveals how this crisis is entangled with cultural assumptions and broader socio-economic structures. Drawing on virtue ethics, the authors argue that if ZOAQs are to genuinely facilitate pro-environmental behaviour change, they must reimagine the current focus of many conservation programs and embed virtues such as compassion, humility, honesty, and respect into all institutional practices, serving as moral role models. This includes critically engaging with food systems, one of the key drivers of loss of place. By embracing this transformative role, ZOAQs can contribute to the structural and ethical changes required to counter species extinction and foster coexistence within the greater community of life.